The Communication Pattern of Government in Socializing the Creative City Campaign as City Branding - Romli, Nada Arina; Akbar, M. Fikri (Penerbit Goodwood, 2025)
Purpose: This study aims to determine the communication patterns used by the Cimahi city government and related agencies to promote the “Creative City” program. Research Methodology: The study employs a qualitative research method using a case study approach, allowing an in-depth exploration of the subject matter within its real-life context. Results: The communication patterns carried out by the Cimahi city government and various parties involved in the Creative City campaign are divided into interpersonal and group communication patterns through business forums, organizational communication patterns, mass communication patterns with conventional media and mass communication patterns with new media. Conclusions: In an effort to create a mutual agreement or social institution in a society, socialization is needed from the organizers in this case the Cimahi City Government which is categorized into two, namely SMEs as the main target and the wider community with interpersonal communication patterns: Business Meeting Forum, Group Discussion Forum, and exhibitions. The organizational communication pattern is the government to the group then the chairman, secretary or information distributor provides information to members using social media such as Facebook, BBM, WhatsApp, and posters. Limitations: This study did not measure the impact of the program on the target audience. Contributions: The benefit of this research is to provide a reference for government institutions to create effective city branding program socialization in disseminating information and gaining high publicity.